Faktor – Faktor Yang Mempengaruhi Literasi Keuangan Digital Siswa : Peran Pendidikan di Keluarga Sebagai Mediasi - Fadilla, Rizky Dwi; Harsono, Harsono (Jurnal Ecogen, 2024)
A high level of digital financial literacy holds significant importance for all individuals, particularly students. This is because possessing proficient digital financial literacy enables individuals to effectively utilize digital financial services.. The aim of this research is to analyze and identify the influence of social media use, pocket money income through family education on high school students. This study employs a quantitative methodology, utilizing questionnaires disseminated through Google Form for data gathering to 100 respondents with a sampling technique using random sampling.  The testing of hypotheses was conducted employing a Structural Equation Model methodology utilizing Partial Least Squares using SmartPLS 3.0 software. The results of research on the use of social media and pocket money income mediated by family education have a significant influence on digital financial literacy among students